badge image

Enroll For Free Now & Improve Your Performance.

×
User Icon
User Icon
User Icon
User Icon
User Icon

Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
Menu
Grade: 12

                        

Q3....................................................(just to reach min. char. limit

4 years ago

Answers : (1)

mycroft holmes
272 Points
							
\because a\ge -1, (a+1)(a^2-2a+1)\ge 0 and hence we have
 
a^3 -a^2 -a +1 \ge 0 \Rightarrow a^3+1 \ge a^2+a
 
and so
 
\sum a^2+a \le \sum a^3+1 = 1+3 = 4
 
i.e. a+b+c+a^2+b^2+c^2 \le 4
 
Equality can occur when a,b,c \in \{1,-1 \} and since require that a^3+b^3+c^3 = 1 this means we can choose a=b=1 and c=-1 and permutations of this as the equality case.
4 years ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies


Course Features

  • 731 Video Lectures
  • Revision Notes
  • Previous Year Papers
  • Mind Map
  • Study Planner
  • NCERT Solutions
  • Discussion Forum
  • Test paper with Video Solution


Course Features

  • 101 Video Lectures
  • Revision Notes
  • Test paper with Video Solution
  • Mind Map
  • Study Planner
  • NCERT Solutions
  • Discussion Forum
  • Previous Year Exam Questions


Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!! Click Here for details